Factorable Surfaces in Pseudo-Galilean Space with Prescribed Mean and Gaussian Curvatures - Sepet, Sezin Aykurt; Bozok, Hülya Gün; Aydin, Muhittin Evren (My University, 2022)
We study the so-called factorable surfaces in the pseudo-Galilean space, the graphs of the product of two functions of one variable. We then classify these surfaces when the mean and Gaussian curvatures are functions of one variable.
Keywords: Fizik; Matematik